Víctimas de trata de personas versus migrantes en situación irregular. Retos y lineamientos para la atención y protección de las víctimas de trata de personas extranjeras en el Perú - Blanco, Cristina (2017)
The text aims to identify aspects that should be considered in preparing the State’s institutions to effectively combat human trafficking of a transnational nature. It addresses four main issues. First, it notices the specific problems of foreign human trafficking victims, which could be confused or overlapped with other categories, such as migrant smuggling and illegal migrant status. Subsequently, it develops three fundamental arguments that give primacy to their status as victims of human trafficking and their specialized attention from a human rights perspective. Thirdly, it provides guidelines on the elements that should constitute this approach from the specific rights of foreign victims of human trafficking. Finally, the Peruvian legal and institutional framework is analyzed, as well as its possibilities and challenges for adequate attention to foreign victims of trafficking.